Comparison of thermal conductivity of traditional and PET reinforced adobe masonry units to improve thermal comfort in buildings - Hancco Chire, Luis; Mansilla Cárdenas, Irwin; Delgado Meneses, Patricia; Ibárcena Ibárcena, Valkiria (LACCEI, 2026)
The objective of the research was to improve adobe masonry units reinforced with recycled PET to create an ecological material with the addition of aloe that can be applied in buildings in cold climates with thermal discomfort. For this purpose, a basic experimental methodology was used, based on traditional empirical techniques, with the use of a thermal camera to determine the thermal conductivity. The results show a better behavior of the material created with 10% of Polyethylene terephthalate (PET) clay soil, which is the most efficient because it can absorb more heat energy and transmit heat, as opposed to traditional adobe samples. This research presents a significant contribution by establishing the ancestral dosages, little known in the scientific field, from a basic experimentation process.